Long-term follow-up of patients on home parenteral nutrition in Europe: implications for intestinal transplantation. Issue 1 (10th November 2010) - Pironi, Loris; Joly, Francisca; Forbes, Alastair; Colomb, Virginie; Lyszkowska, Malgorzata; Baxter, Janet; Gabe, Simon; Hébuterne, Xavier; Gambarara, Manuela; Gottrand, Frederic; Cuerda, Cristina; Thul, Paul; et al.
Abstract : Background: The indications for intestinal transplantation (ITx) are still debated. Knowing survival rates and causes of death on home parenteral nutrition (HPN) will improve decisions. Methods: A prospective 5-year study compared 389 non-candidates (no indication, no contraindication) and 156 candidates (indication, no contraindication) for ITx. Indications were: HPN failure (liver failure; multiple episodes of catheter-related venous thrombosis or sepsis; severe dehydration), high-risk underlying disease (intra-abdominal desmoids; congenital mucosal disorders; ultra-short bowel), high morbidity intestinal failure. Causes of death were defined as: HPN-related, underlying disease, or other cause. Results: The survival rate was 87% in non-candidates, 73% in candidates with HPN failure, 84% in those with high-risk underlying disease, 100% in those with high morbidity intestinal failure and 54%, in ITx recipients (one non-candidate and 21 candidates) (p<0.001). The primary cause of death on HPN was underlying disease-related in patients with HPN duration ≤2 years, and HPN-related in those on HPN duration >2 years (p=0.006). In candidates, the death HRs were increased in those with desmoids (7.1; 95% CI 2.5 to 20.5; p=0.003) or liver failure (3.4; 95% CI 1.6 to 7.3; p=0.002) compared to non-candidates. In deceased candidates, the indications for ITx were the causes of death in 92% of those with desmoids or liver failure, and in 38% of those with other indications (p=0.041). In candidates with catheter-related complications or ultra-short bowel, the survival rate was 83% in those who remained on HPN and 78% after ITx (p=0.767). Conclusions: HPN is confirmed as the primary treatment for intestinal failure. Desmoids and HPN-related liver failure constitute indications for life-saving ITx. Catheter-related complications and ultra-short bowel might be indications for pre-emptive/rehabilitative ITx. In the early years after commencing HPN a life-saving ITx could be required for some patients at higher risk of death from their underlying disease.